2020
DOI: 10.7717/peerj.10147
|View full text |Cite
|
Sign up to set email alerts
|

A 22-amino-acid peptide regulates tight junctions through occludin and cell apoptosis

Abstract: Occludin is a structural protein of tight junctions (TJ) in the blood–testis barrier (BTB). A 22-amino-acid peptide (22AA) in the second extracellular loop can reversibly regulate TJ, but its regulatory mechanism is unknown. In this study, a 22AA-induced TJ destruction animal model was constructed to investigate the effect of 22AA on Sertoli cells (SCs) and spermatid counts and cell apoptosis at different time points using a multiplex immunofluorescence technique. The effect of 22AA on the location and distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The BTB loses its integrity when the tight link between Sertoli cells is broken, resulting in spermatogenesis problems. Some important key proteins or components are constantly being discovered, such as PTBP1 ( Yang et al, 2021 ), noncollagenase domain (NC1)-peptide ( Liu et al, 2021 ), a 22-amino-acid peptide (22AA) ( Zhu et al, 2020 ), ubiquitously expressed transcript ( Thomas et al, 2020 ), TBC1D20 ( Thomas et al, 2020 ), SENP3 ( Wu et al, 2017 ), BT-IgSF ( Pelz et al, 2017 ), Pin1 ( Islam et al, 2017 ), ANXA2 ( Chojnacka et al, 2017 ), AKAP9 ( Venkatesh et al, 2016 ), GATA4 ( Schrade et al, 2016 ), and intercellular adhesion molecule-1 ( Mruk, 2016 ), that are required for the structural integrity of the BTB. Regulation of BTB dynamics is also an important research area.…”
Section: Discussionmentioning
confidence: 99%
“…The BTB loses its integrity when the tight link between Sertoli cells is broken, resulting in spermatogenesis problems. Some important key proteins or components are constantly being discovered, such as PTBP1 ( Yang et al, 2021 ), noncollagenase domain (NC1)-peptide ( Liu et al, 2021 ), a 22-amino-acid peptide (22AA) ( Zhu et al, 2020 ), ubiquitously expressed transcript ( Thomas et al, 2020 ), TBC1D20 ( Thomas et al, 2020 ), SENP3 ( Wu et al, 2017 ), BT-IgSF ( Pelz et al, 2017 ), Pin1 ( Islam et al, 2017 ), ANXA2 ( Chojnacka et al, 2017 ), AKAP9 ( Venkatesh et al, 2016 ), GATA4 ( Schrade et al, 2016 ), and intercellular adhesion molecule-1 ( Mruk, 2016 ), that are required for the structural integrity of the BTB. Regulation of BTB dynamics is also an important research area.…”
Section: Discussionmentioning
confidence: 99%
“…1 (b). The cells were filled with WT1 which was one of marker protein of SCs [ 26 ]. The results suggested that the isolated cells were SCs.…”
Section: Resultsmentioning
confidence: 99%
“…The slides were block with peroxidase for 5 min and washed as above. The slides were incubated for 30 min with the primary anti-Wilms tumor protein1(anti-WT1) [ 26 ] (1:100 dilution, abcam, USA). After washed three times with phosphate buffer saline (PBS) for 3 min each, the horseradish peroxidase-labeled secondary antibody (1:800 dilution, abcam, USA) was added dropwise, then incubated at 37 °C for 30 min, followed by the substrate-chromogen solution (3,3′-diaminobenzidine), and finally counter stained with hematoxylin.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation